Analisis Implementasi Pendidikan Karakter Dalam Membentuk Sikap Sosial Perseta Didik Melalui Pembelajaran IPS Terpadu Di SMPN 21 Kota Bengkulu - Sazili Sazili; Zufiyardi Zufiyardi; Yensi Ekaputri (Universitas Dehasen Bengkulu, 2024)
The progress of a nation is largely determined by the quality of its national character, national character is a very important component of human resources. The Indonesian National Education System Law is an important document that highlights the role of national education in helping to develop potential and shape the character and civilization of the nation's next generation. in an effort to increase the intelligence of the country's life. This study aims to determine the implementation of character education in building students' social attitudes through integrated Social Studies Learning Class VIII at SMPN 21 Bengkulu City This study used a descriptive qualitative approach. The technique collecting data used observation, interview and documentation.The research results indicate as follows: (1) the process of implementing character education in buliding students' social attitudes through Integrated Social Sciences learning for class VIII 2 SMPN 21 Bengkulu is carried out by integrating character education with Integrated Social Sciences subjects and instilling character values in every lesson that takes place so that students' social attitudes can be formed, (2) social attitudes formed in class VIII 2 include: honesty, responsibility, tolerance, mutual cooperation, politeness and self-confidence, (3) assessment carried out by the teacher by using a students’ attitude observation sheet which is divided into four items, namely self-assessment, peer assessment, observation and journal.